Diego Hurtado de Mendoza, Poesía erótica. Edición de J. Ignacio Díez Fernández. Ediciones Aljibe, Málaga, 1995; 220 pp. (Erótica Hispánica, 3). - Santibáñez Escobar, Julia (El Colegio de México, 1998)
Se reseñó el libro: Poesía erótica.